Chapter 0: Section 0.1 - Part 1

1.  "It is not difficult to find a formula for Fn"

(1)  The standard recurrence relation for Fibonnaci number n is:

  • F0=0
  • F1=1
  • For n2
Fn=Fn1+Fn2

(2)  The formula for n is as follows:

Fn=15((1+52)n(152)n)

Notes:

  • The derivation and elementary proofs are detailed here.

Exercises:

1.  Exercise 0.1.1:  (a)  Use the recurrence relation for the fibonacci numbers, and induction to prove that every Fibonacci number is an integer.

Solution:
  • S(1) is true since F1=1 is an integer.
  • We assume that S(k) is true, that is, S(k) is an integer.
  • S(k+1) = S(k) + S(k-1) which is an integer since the sum of two integers is an integer by the closure property on addition.  See here for properties of integers.

2.  Exercise 0.1.1: (b) Prove that Binet's Formula is correct by verifying that it holds for n=0,1 and then, for all larger integers n by induction.

Solution:
  • S(0) is true since F0=15((1+52)0(152)0)=0
  • S(1) is true since F1=15((1+52)1(152)1)=15(1+51+52)=1
  • We assume that S(k) is true, that is, Fk=15((1+52)k(152)k)
  • S(k+1) is true since Fk+1=Fk+Fk1=15((1+52)k(152)k)+15((1+52)k1(152)k1) 
  • =15((1+52)k(152)k+(1+52)k1(152)k1) 
  • =15((1+52)k1(1+52+1)(152)k1(152+1)) 
  • =15((1+52)k1(3+52)(152)k1(352))
  • =15((1+52)k1(1+52)2(152)k1(152)2)
  • =15((1+52)k+1(152)k+1)

3.  Exercise 0.1.2: Use induction on n1 to prove that (a) F1+F3++F2n1=F2n

Solution:
  • S(1) is true since F1=1=F2=F2(1)
  • We assume that S(k) is true, that is, F1+F3++F2n1=F2n
  • F2n+2=F2n+1+F2n=F2n+1+F2n1++F3+F1
4.  Exercise 0.1.2:  Use induction on n1 to prove that (b) 1+F2+F4++F2n=F2n+1

Solution:
  • S(1) is true since 1+F2=1+1=2=F1+F2=F3
  • We assume that S(k) is true, that is,  1+F2+F4++F2n=F2n+1
  • F2n+3=F2n+2+F2n+1=F2n+2+F2n++F4+F2+1
5.  Exercise 0.1.3: The number ϕ=1+52 is called the golden ratio(a) Prove that ϕ2=ϕ+1

Solution:
  • ϕ2=(1+52)2=3+52=1+52+1
6.  Exercise 0.1.3: (b) Prove that ϕn=Fnϕ+Fn1 for all integers n1, by induction

Solution:
  • S(1) is true since ϕ1=1+52=F1ϕ+F0
  • We assume that S(k) is true, that is, ϕn=Fnϕ+Fn1 for all integers n1
  • ϕn+1=ϕϕn=ϕ(Fnϕ+Fn1)=Fnϕ2+Fn1ϕ=Fn(F2ϕ+F1)+Fn1ϕ=Fnϕ+Fn+Fn1ϕ
  • =Fn+1ϕ+Fn  






Comments

Popular posts from this blog

Notes on Andrew Granville's Number Theory: A Masterclass